Mangunwijaya's Concept of Religiosity in His Architectural Work of Gereja Maria Assumpta (GMA), Klaten-Indonesia - Mahamboro, Dionius Bismoko; Hadi, Romualdus Setyo; Pabubung, Michael Reskiantio (Indonesian Center for Religion and Society Studies (InTReSt), 2024)
Yusuf Bilyarta Mangunwijaya (often referred to as Romo Mangun; YBM) stands out as one of Indonesia’s architectural luminaries, and his architectural vision is deeply rooted in his religious background as a Catholic priest. This article delves into the intrinsic religious values embedded within one of Romo Mangun’s architectural masterpieces, the Church of Maria Assumpta or Gereja Maria Assumpta (GMA) in Klaten. This structure emanates a profound and sanctified ambiance by merging traditional Javanese architectural elements with a contemporary sensibility. By adopting a qualitative approach, explicitly employing a constructivist paradigm of symbolic interactionism and phenomenology theoretical schools, this research raises a question on how Mangunwijaya engraved his understanding and discernment of religiosity in his architectural work of GMA. By using Mangunwijaya’s GMA as a material object and his concept of religiosity as a formal object, it is found that he engraved his understanding and discernment of religiosity through his architectural work of GMA. To be religious is (1) to be a part of our own culture, which is shown by the space order; (2) to be focused on the Most High, shown by the orientation, ornaments, and liturgical light and colors; and (3) living in harmony, well-engraved in the proportion.